Kampanye digital, FoMO, dan kesadaran politik di kalangan generasi Z: Bukti dari gerakan viral “Brave Pink” - Habib, Ahmad Fuad; Pratama, David Rino; Wijayanti, Yani Tri (Jurnal Mahasiswa Komunikasi Cantrik, 2026)
This study aims to analyze the influence of the Brave Pink campaign on the political awareness of Generation Z with Fear of Missing Out (FoMO) as a mediating variable. The study used a quantitative approach with a survey design of 396 followers of the Instagram account @barengwarga. Data analysis was carried out using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach. The results showed that the Brave Pink campaign had a significant effect on Fear of Missing Out (β = 0.910; p < 0.001) and a direct effect on political awareness (β = 0.622; p < 0.001). Fear of Missing Out also had a significant effect on political awareness (β = 0.370; p < 0.001) and acted as a partial mediator. The research model has very strong predictive power with an R² value of 0.943. This study provides a theoretical contribution by developing the Uses and Effects framework in the context of digital political communication, specifically through the integration of Fear of Missing Out (FoMO) as a psychological mechanism that bridges the relationship between exposure to symbolic digital campaigns and the formation of political awareness.